2021
DOI: 10.1007/s40534-021-00262-x
|View full text |Cite
|
Sign up to set email alerts
|

Seismic analysis of high-speed railway irregular bridge–track system considering V-shaped canyon effect

Abstract: To explore the effect of canyon topography on the seismic response of railway irregular bridge–track system that crosses a V-shaped canyon, seismic ground motions of the horizontal site and V-shaped canyon site were simulated through theoretical analysis with 12 earthquake records selected from the Pacific Earthquake Engineering Research Center (PEER) Strong Ground Motion Database matching the site condition of the bridge. Nonlinear seismic response analyses of an existing 11-span irregular simply supported ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Topography also plays a role in the earthquake effect results. Zhu et al [114] found neglecting the effect of V-shaped canyon leads to the inappropriate assessment of the maximum seismic response of the ( 7) 15 Schematic diagram of train-bridge system subjected to earthquake [107] irregular high-speed railway. It is well known that both track irregularities and seismic motions are random in nature.…”
Section: Effect Of Earthquake Excitationmentioning
confidence: 99%
“…Topography also plays a role in the earthquake effect results. Zhu et al [114] found neglecting the effect of V-shaped canyon leads to the inappropriate assessment of the maximum seismic response of the ( 7) 15 Schematic diagram of train-bridge system subjected to earthquake [107] irregular high-speed railway. It is well known that both track irregularities and seismic motions are random in nature.…”
Section: Effect Of Earthquake Excitationmentioning
confidence: 99%
“…found that a V‐shaped canyon may significantly increase the seismic response of beams, piers and supports of a bridge with aid of the OpenSees software. Zhu et al 22 . also pointed out the necessity to consider the topography in estimating the seismic response of irregular railway bridge‐track systems in a V‐shaped canyon during the seismic design and analysis of a bridge by using a numerical model in the OpenSees.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al 21 found that a V-shaped canyon may significantly increase the seismic response of beams, piers and supports of a bridge with aid of the OpenSees software. Zhu et al 22 also pointed out the necessity to consider the topography in estimating the seismic response of irregular railway bridgetrack systems in a V-shaped canyon during the seismic design and analysis of a bridge by using a numerical model in the OpenSees. Liu et al 23 proposed a hybrid boundary element and finite element method to investigate the stochastic seismic response of long-span bridges in a fluid-saturated poroelastic canyon.…”
Section: Introductionmentioning
confidence: 99%
“…To reduce land coverage, the rule of "substituting a bridge for subgrade" is often adopted in the design and construction of high-speed railways. Bridges account for up to 70%-80% of the entire rail line in terms of length, and most are short-span bridges [1][2][3][4][5][6]. erefore, selecting the optimal earthquake resisting scheme for short-span bridges is crucial to maximizing the safety, serviceability, and economy of high-speed railways in high seismic intensity regions.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the weight of the superstructure should be reduced to minimize the seismic response. Prestressed concrete (PC) simply-supported box beams are generally implemented for short-span bridges in China's high-speed railways [1][2][3][4][5][6], whereas reinforced concrete (RC) rigid frame bridges are adopted for Japanese Shinkansen railways on a large scale [7,8], and steel-concrete composite (SC) beams are often used in France [1].…”
Section: Introductionmentioning
confidence: 99%